Pregnancy rate, maternal and neonatal outcomes among breast cancer survivors: A systematic review - Marzieh Azizi; Elham Ebrahimi; Zahra Behboodi Moghadam; Zohreh Shahhosseini; Maryam Modarres (Wiley, 2023)
Abstract Aim This study investigated the pregnancy rate, maternal and neonatal outcomes, and breast cancer (BC) recurrence status after pregnancy among BC survivors. Design A systematic review. Methods Electronic databases such as PubMed, Web of Science [WOS], Scopus, ScienceDirect, Google Scholar, and Scientific Information Database were systematically searched. The quality of included studies was evaluated using the Newcastle-Ottawa Scale (NOS). Observational studies reported the pregnancy rate, maternal and neonatal outcomes among reproductive‐aged BC survivors, and the recurrence status of BC after pregnancy were eligible to include in this study. Results Of the 29 included studies, 13 studies were prospective cohorts or prospective multicenter or population‐based cohorts, 14 studies were retrospective cohort or retrospective population‐based cohort studies, and two studies were cross‐sectional retrospective surveys or population‐based descriptive studies. This systematic review showed that the pregnancy rate was estimated at 3.1%-48.5% among BC survivors who attempted to conceive. The most prevalent maternal outcomes of pregnancy were miscarriage (1.8%-33.3%) and induced abortion (5.0%-44%) as well as preterm birth (PTB) or very PTB (1.2%-21.1%), and twin birth (1.1%-38.8%) were the most prevalent neonatal outcomes occurring among BC survivors, respectively. In addition, most of the included studies indicated that pregnancy had no adverse effect on the status of BC recurrence among survivors. Surviving women can be encouraged and receive a carefully multidisciplinary approach regarding healthy pregnancy. No Patient or Public Contribution.